PENGARUH GAYA BELAJAR DAN SIKAP DISIPLIN TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Maria Dorotea Due; Stefania Baptis Seto; Ningsih Ningsih (Program Studi Pendidikan Matematika, 2023)
This study aims to find out:(1) whether or not there is an influence of learning style on mathematics learning outcomes; (2) whether or not there is an influence of disciplinary attitudes on mathematics learning outcomes; (3) where there is a significant influence between learning styles and disciplinary attitudes towards mathematics learning outcomes The type of research use quantitative research. The sample in this study was 44. The instrument use disaquestion naire. Analysis preset test (normality test, linearity test and multicolour linearity test), multiple linear regression analysis test and hypothesis test (t-test and F test). From the result of the study, it can be concluded that (1)There is no influence of learning style on mathematics learning outcomes. (2) There is no influence of disciplinary attitudes on mathematics learning outcomes, (3)There is no influence between learning styles and disciplinary attitudes on mathematics learning outcomes. The price of the beta coefficient of the learning style variable is -0,279, the learning environment variable is 0,293 and the constant value is 77,744. So the regression equationY= 77,44 + (-0,279)X1+0,293X2 which means the constant value is 77,744.